Nine Ways of Looking at Ourselves (Looking at Cities) - Goldbard, Arlene (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
This essay appears in What We See: Advancing the Observations of Jane Jacobs (New Village Press 2010), an anthology co-published by New Village Press and The Center for the Living City collecting original essays by leading thinkers to honor the late Jane Jacobs, best-known for her first book, The Death and Life of Great American Cities. This essay explores nine different ways our own habits of perception affect our view of the culture of cities and their possible futures. An interactive website has been created for What We See at: www.whatwesee.org. Reprinted in this issue of Culture and Local Governance with permission of the author and New Village Press.